Strategic Research Trials on Genotype × Environment × Management in Major Cropping Systems using Advance Generation Genotypes and Mega-varieties - Devkota Wasti, Mina Kumari; Abdulraman, Rehab; El Amil, Rola; Idris, Amani A. M.; Moussadek, Rachid; Attaher, Samar; Omar, Mohie; Devkota, Krishna; Juraev, Diyor; Elmarzak, Mohcin; Slimani, Mohammed (International Center for Agricultural Research in the Dry Areas, 2022)
Declining rainfall with an increasing variability, increasing temperature extremes, and declining soil fertility are threatening crop production and ultimately food security in the CWANA region. Also, the presence of higher attainable/management yield gaps in the region indicates the possibility of improving crop productivity by adopting improved variety and agronomic practices. Due to significant Genotype (G) × Environment (E) × Management (M) interaction, the development of suitable and broadly adapted varieties is complicated and resource consuming. Understanding the interaction effect between genotype and agronomic management practices on crop growth and productivity is critical to achieving stable yields under variable bio physical and socio-economic environments. In this response, in collaboration with the national research centers and F2-R CWANA WP3, strategic G × E × M experimentation has been designed and established in 2022 in different wheat-based production systems in five CWANA countries, Egypt, Lebanon, Morocco, Sudan, and Uzbekistan. The objective of this collaborative research is to generate standard data set for developing the bundled agronomic solution of diverse production environments through different analytical methods; and help to develop a breeding product profile to inform breeders for developing breeding strategy.